Green Energy Policy Implementation in Bali: Challenges and Opportunities - Antari, Ni Putu Bayu Widhi; Pinatih, I.G.A.A. Dewi Sucitawathi; Joniarta, I Wayan (Bali Membangun Bali: Jurnal Bappeda Litbang, 2025)
Purpose: This study aims to explain the implementation of green energy policies in Bali as a popular international tourist destination as well as identify various opportunities and challenges faced by the Bali Provincial Government in implementing green energy policies. Research methods: The study utilizes qualitative methods by conducting interview and collecting secondary data. Qualitative data analysis is carried out by making verbatims, reducing the unimportant discussion, coding the discussion, and classifiying to the themes. Findings: Bali provincial government enacted some green energy policies, but in term of sustainable waste management, the policy should regulate about how landfill is built and how the gas is converted to the energy. Implication: The hurdles are enough capacity of fossil energy sources, bad experience in wind power establishment, and lack of government financial supports.